Modeling the energy future. (6th November 2017) - Case, James
Abstract : Abstract: A bare‐bones dynamic model of an island economy is constructed for the purpose of discovering "socially optimal" fossil fuel depletion schedules. An entire family of candidates is identified, all members being significantly more gradual than the one currently in force. The active ingredient in the model is a real‐valued function of two real variables―the current extraction rate and the quantity extracted to date―which quantifies the need to expend energy in the course of delivering it to end users. The main conclusions are that fossil fuels are currently being extracted far too fast for the common good, while a wide variety of socially preferable schedules are overlooked. Summary for Managers: Consider conservation! Several methods have proven successful in the past. Before World War I, Standard Oil did it by monopolizing the industry. During the 1930s, the Texas Railroad Commission invoked martial law. OPEC has achieved intermittent success by forming a cartel. The proposed carbon tax may be the fairest alternative. Any method of slowing the extraction of fossil fuels will encounter resistance, as the public has long been addicted to cheap energy. Yet conservation will slow global warming, even as it economizes an increasingly scarce resource. Expect no painless alternative― there is none !